Peer-review of monograph “African swine fever in strict nature reserves (case study of Voronezh nature reserve)”. B. V. Romashov, N. B. Romashova, E. A. Starodubtseva, A. S. Mishin. Voronezh: Publishing and polygraphic center “Science Book”, 2019. 120 p. ISBN 978-5-4446-1236-1 - V. V. Makarov (Ветеринария сегодня)
.